Synthesis and Characterization of a Hydroxyapatite-Sodium Alginate-Chitosan Scaffold for Bone Regeneration - Liu, Dingkun; Liu, Zhihui; Zou, Jundong; Li, Lingfeng; Sui, Xin; Wang, Bizhou; Yang, Nan; Wang, Bowei (Frontiers in Materials, 2021)
Bone scaffolds play an important role in promoting the healing of large bone defects. However, the type of scaffold material, type of drug loaded into the scaffold, and method of preparation have a significant impact on the scaffold’s properties. In this study, we developed a composite scaffold comprising sodium alginate (SA), chitosan (CS), and hydroxyapatite (HA). The composite stent carries vascular endothelial growth factor (VEGF), wrapped in internal microspheres, and vancomycin (VAN). The microspheres are wrapped in an outer matrix formed by SA, CS, and HA, whereas the outer matrix carries VAN. Using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction, and scanning electron microscopy analyses, we studied the contraction rate, swelling, porosity, mechanical properties, degradation, and drug release ability of all the composite scaffolds. The best scaffold, as demonstrated by the results of these studies, was the HA6(SA/CS)4@VAN/VEGF scaffold. The antibacterial ability of the HA6(SA/CS)4@VAN/VEGF scaffold was determined using Staphylococcus aureus (S. aureus). Cytotoxicity, cell adhesion, and osteogenic properties of the HA6(SA/CS)4@VAN/VEGF scaffold were studied using bone marrow mesenchymal stem cells. The results indicate that the HA6(SA/CS)4@VAN/VEGF scaffold exhibits good physical, chemical, antibacterial, and osteogenic properties, and is, thus, a new type of bone scaffold composite material with good osteogenic potential.